Multi‐seasonal modelling of plant‐nematode interactions reveals efficient plant resistance deployment strategies. (22nd May 2020) - Nilusmas, Samuel; Mercat, Mathilde; Perrot, Thomas; Djian‐Caporalino, Caroline; Castagnone‐Sereno, Philippe; Touzeau, Suzanne; Calcagno, Vincent; Mailleret, Ludovic
Abstract: Root‐knot nematodes, Meloidogyne spp ., are soil‐borne polyphagous pests with major impact on crop yield worldwide. Resistant crops efficiently control avirulent root‐knot nematodes, but favour the emergence of virulent forms. Since virulence is associated with fitness costs, susceptible crops counter‐select virulent root‐knot nematodes. In this study, we identify optimal rotation strategies between susceptible and resistant crops to control root‐knot nematodes and maximize crop yield. We developed an epidemiological model describing the within‐season dynamics of avirulent and virulent root‐knot nematodes on susceptible or resistant plant root‐systems, and their between‐season survival. The model was fitted to experimental data and used to predict yield‐maximizing rotation strategies, with special attention to the impact of epidemic severity and genetic parameters. Crop rotations were found to be efficient under realistic parameter ranges. They were characterized by low ratios of resistant plants and were robust to parameter uncertainty. Rotations provide significant gain over resistant‐only strategies, especially under intermediate fitness costs and severe epidemic contexts. Switching from the current general deployment of resistant crops to custom rotation strategies could not only maintain or increase crop yield, but also preserve the few and valuable R‐genes available.